Hubungan antara Perilaku Perundungan dengan Kesehatan Mental Siswa SMP - Siti Nurhayatun; Arri Handayani; Venty Venty (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the relationship between bullying behavior and the mental health of junior high school students. Adolescence is a developmental phase particularly vulnerable to bullying, which can impact students' psychological well-being and mental health. A quantitative correlational approach was employed. The study population consisted of 210 junior high school students, with a sample of 138 students determined using Slovin's formula and simple random sampling. Data were collected via Likert-scale questionnaires and documentation. Normality tests revealed that the bullying behavior variable was normally distributed (Sig. = 0.077), whereas the mental health variable was not (Sig. = 0.000); consequently, the Spearman Rank correlation test was used for data analysis. The results showed a significance value of 0.000 (p < 0.05) and a correlation coefficient of -0.440, indicating a moderate negative relationship between bullying behavior and student mental health. Higher levels of bullying behavior experienced by students corresponded to lower levels of mental health; conversely, lower levels of bullying behavior were associated with better mental health. The study highlights the need to strengthen bullying prevention efforts through guidance and counseling services, as well as collaboration among schools, teachers, parents, and the entire school community, to create a safe learning environment that supports student mental health.